Functional hepatic deterioration determined by 13C-methacetin breath test is associated with impaired hemodynamics and late Fontan failure in adults - Schleiger, Anastasia; Kramer, Peter; Sallmon, Hannes; Jentsch, Niklas; Pileckaite, Marta; Danne, Friederike; Schafstedde, Marie; Müller, Hans-Peter; Müller, Tobias; Tacke, Frank; Jara, Maximilian; Stockmann, Martin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Despite improved survival a substantial number of Fontan patients eventually develop late failure. Fontan-associated liver disease (FALD) is the most frequent end-organ dysfunction. Although impaired hemodynamics and Fontan failure correlate with FALD severity, no association between hepatic functional metabolic impairment and Fontan hemodynamics has been established. Hypothesis Metabolic liver function measured by liver maximum function capacity test (LiMAx®) correlates with Fontan hemodynamics and Fontan failure. Methods From 2020 to 2022, 58 adult Fontan patients [median age: 29.3 years, IQR (12.7), median follow-up time after Fontan operation: 23.2 years, IQR (8.7)] were analyzed in a cross-sectional study. Hemodynamic assessment included echocardiography, cardiopulmonary exercise testing and invasive hemodynamic evaluation. Fontan failure was defined based on commonly applied clinical criteria and our recently composed multimodal Fontan failure score. Results LiMAx® test revealed normal maximum liver function capacity in 40 patients (>315 μg/h*kg). In 18 patients a mild to moderate impairment was detected (140–314 μg/h*kg), no patient suffered from severe hepatic deterioration (≤ 139 μg/kg*h). Fontan failure was present in 15 patients. Metabolic liver function was significantly reduced in patients with increased pulmonary artery pressure (p = 0.041. r = −0.269) and ventricular end-diastolic pressure (p = 0.033, r = −0.325), respectively. In addition, maximum liver function capacity was significantly impaired in patients with late Fontan failure (289.0 ± 99.6 μg/kg*h vs. 384.5 ± 128.6 μg/kg*h, p = 0.007). Conclusion Maximum liver function capacity as determined by LiMAx® was significantly reduced in patients with late Fontan failure. In addition, elevated pulmonary artery pressure and end-diastolic ventricular pressure were associated with hepatic functional metabolic impairment.